Lycian Wooden Huts and Sign 24 on the Phaistos Disc - Mellink, Machteld J.
“One resemblance to Bronze Age Lycian architecture does not vindicate Evans’ theory of a Lycian origin for the Phaistos Disc but it helps to keep it alive”, p. 7.